Digital mapping and spatial characteristics analyses of heavy metal content in reclaimed soil of industrial and mining abandoned land. Issue 1 (December 2018) - Zhang, Shiwen; Liu, Huilin; Luo, Ming; Zhou, Xu; Lei, Mei; Huang, Yuanfang; Zhou, Yan; Ge, Chang
Abstract The reclaimed soil properties of industrial and mining wasteland have strong spatial specificity. The paper aimed to screen out a hybrid multifractal and kriging (Named as Mkriging) method for digital mapping and scientifically reveal the spatial distribution characteristics in view of heavy metal in reclaimed soil of industrial and mining abandoned land. The results of the study showed that for reasons of history and reclamation, the original samples of heavy metals in reclaimed soil of industrial and mining abandoned land showed a very large range and variation degree, theC 0 /(C 0 + C 1 ) values of different heavy metals basically were all greater than 50%, random factors played a dominant role. The five kinds of heavy metals in reclaimed soil were in the following descending order in terms of homogeneity: Cd, As, Hg, Ni and Cr. Compared with ordinary Kriging method, the relative improvement of root mean squared errors of elements Cd, Hg, As, Cr and Ni based on Mkriging were 95.28%, 61.74%, 78.54%, 82.51% and 83.58% respectively. The higher the fractal degree of heavy metals in reclaimed soil was, the higher the prediction accuracy will be. Mkriging method is more suitable for spatial prediction of heavy metals in reclaimed soil of industrial and mining abandoned land.